THE POTENTIAL OF ARTICLE 259 TFEU AS A TOOL FOR UPHOLDING THE MUTUAL TRUST IN THE EU - Hristina Runcheva Tasev; Milena Apostolovska Stepanoska; Leposava Ognjanoska (Faculty of Law Osijek, 2022)
The principle of mutual trust, whose fundamental importance is recognized by the CJEU, is not mentioned in the Treaties, but nonetheless, it plays an essential role for the EU integration process and has become a structural principle of the EU law. In addition to its role as a basis for a large set of EU rules in the areas such as the internal market and the area of freedom, security and justice, this principle is also closely related to the EU founding values including the rule of law. Having in mind that is not a “blind trust” but an assumption, it is applied through ensuring compliance with the Union law for which both the Member States and the European Commission share responsibility, inter alia, by means of the infringement procedure. Under Article 259 TFEU, Member States are also entitled to bring a direct action against another Member State for an alleged infringement of an obligation under the Treaties. How- ever, it is extremely rare for a Member State to take action upon the Article 259 TFEU and its potential remains untapped till now. This contribution aims to answer why do Member States are inactive in terms of invoking the infringement procedure. It argues that infringement procedure initiated by a Member State against another Member State should not be perceived as a violation of the mutual trust between them but as a tool to uphold the mutual trust and to protect the Union’s founding values, including the rule of law.
Vol. 6 (2022): THE RECOVERY OF THE EU AND STRENGTHENING THE ABILITY TO RESPOND TO NEW CHALLENGES – LEGAL AND ECONOMIC ASPECTS
Keywords: Article 259 TFEU, Court of Justice of the EU, Member States’ direct actions, mutual trust